Thermal analysis of metal-ceramic bonding using finite element method - Gopinath, S.; Sabarish, R; Sasidharan, R. (International Journal of Engineering and Technology, 2014)
This paper reports a finite element study of effect of bonding strength between metal and ceramic. The bonding strength is evaluated with different processing temperature and holding time. The difference between the coefficients of linear thermal expansion (CTEs) of the metal and ceramic induces thermal stress at the interface. The mismatch thermal stress at the interface region plays an important role in improving bonding strength. Hence, it is essential to evaluate the interface bonding in metal-ceramics joints. The Al/SiC bonding was modeled and analyzed using finite element analysis in ANSYS (v.10).   Keywords: Bonding Strength, Coefficient of Thermal Expansion, Thermal Stress, Interface, Al/Sic, FEA.